Avaliação anatomopatológica de fígado, rim, pulmão e cérebro de camundongos expostos ao composto ditelureto de difenila - Luz, Sônia Cristina Almeida da (2014)
Diphenyl ditelluride (PhTe)2 is an organic tellurium compound widely used as an intermediate in organic synthesis reactions and in the industry. Several studies have shown that this compound causes various toxic effects in different tissues. Particularly notable are teratogenic, genotoxic and neurotoxic effects. Although the mechanisms involved in cytotoxicity mediated by the compound are not fully understood, its pro-oxidant activity is directly related to its toxicology. Inhibition of sulfhydryl enzyme and antioxidant, thiol depletion, and lipid peroxidation are biochemical changes found in tissues such as blood, brain, liver and kidney of animals exposed to the compound. On the other hand, there are few histopathological studies showing the effects of exposure to (PhTe)2 in specific organs. Thus, the present study aimed to carry out the anatomopathological evaluation of the brain, kidney, liver and lung of mice exposed subcutaneously acutely (1 dose of 250 μmol/kg) and subchronically (doses 10 and 50 μmol/kg for 7 and 14 days) to the compound. Histological analysis showed that the hepatocytes of animals exposed subchronically to both doses of the compound developed extensive vacuolization of the cytoplasm or hydropic degeneration and hyperchromatic nuclei. Subchronic exposure to 50μmol/kg has also induced nonspecific focal hepatitis and focal necrosis. Hepatic steatosis was observed in animals acutely exposed to the compound. In the kidney, acute and/or subchronic intoxication with (PhTe)2 caused vacuolar degeneration or hydropic degeneration, atrophy and hypertrophy of renal tubules, forming hyaline casts and acute tubular necrosis. Pulmonar edema and vascular congestion were found in the lungs of animals exposed to (PhTe)2 50μmol/kg. Histological analysis of brain tissue revealed that acute and subchronic exposure to (PhTe)2 induced neurodegenerative disorders (neuropil vacuolation, status spongiosus) in the hippocampus and thalamus. The presence of neuronal nuclear pyknosis, the loss of neuronal viability and neuronal death were observed particularly in the hippocampus. Additionally, through immunohistochemistry, we identified glial reaction and loss of pre-synaptic activity in the thalamus and cortex, corresponding to areas of spongiform change. Our findings suggest that exposure to (PhTe)2, subcutaneously causes severe morphological changes in liver, kidney, lung and brain. The data obtained will contribute significantly to increase the knowledge on the toxicology of the compound (PhTe)2, since this is the first work that evaluates the histology of tissues of various organs after intoxication with the compound.